2020
DOI: 10.3390/app10051695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whole-Body Vibration Training on the Physical Capability, Activities of Daily Living, and Sleep Quality of Older People with Sarcopenia

Abstract: Aim: To investigate the effect of whole-body vibration on older people with sarcopenia, and their physical capability, activities of daily living, and sleep quality. Methods: This study is quasi-experimental and adopts single-group pretest–posttest design. The study included participants aged older than 65 years who lived in nursing homes and care centers in Taipei, Taiwan. The whole-body vibration training was performed for 3 months, and during each training session, a participant received ten cycles of 60-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…WBVT involves the participant standing or sitting on a vibrating platform whilst partaking in isometric strength and balance exercises [77]. WBVT has been infrequently trialled in patients diagnosed with sarcopenia [78][79][80]. The most recent study demonstrated improvements in physical capability following twelve weeks of WBVT.…”
Section: Whole-body Vibration Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…WBVT involves the participant standing or sitting on a vibrating platform whilst partaking in isometric strength and balance exercises [77]. WBVT has been infrequently trialled in patients diagnosed with sarcopenia [78][79][80]. The most recent study demonstrated improvements in physical capability following twelve weeks of WBVT.…”
Section: Whole-body Vibration Trainingmentioning
confidence: 99%
“…The most recent study demonstrated improvements in physical capability following twelve weeks of WBVT. Improvements in onefoot balance, shoulder and arm flexibility, gait speed, hand grip strength, five sit-to-stand repetitions and an increase in muscle mass index were recorded in the participants [80].…”
Section: Whole-body Vibration Trainingmentioning
confidence: 99%
“…The prevalence of sarcopenia is as high as 5–19% [ 10 , 12 , 13 ] in older people without LTCI and 48% in older people with LTCI [ 14 ]. Having sarcopenia has also been shown to be associated with fall and fracture events, decreased activities of daily living (ADL), increased mortality, and increased costs for medical and long-term care insurance [ 15 , 16 , 17 ]. Moreover, older people with LTCI who have sarcopenia are reported to have low physical activity and are presumed to be at very high risk [ 18 ].…”
Section: Introductionmentioning
confidence: 99%